State development bank of CHINA: Contribution to PRC sustainable economic growth - S. S. Matveevskii; K. T. Tazabaeva (Вестник университета)
The paper presents a description of the activities of the State Development Bank of China (GBRK). The author reveals the structure of the bank’s owners; GBRK mainly implements projects in the field of infrastructure, agriculture and industry, innovation both in China and abroad. The Bank finances its activities primarily through the issuance and sale of bonds. The growth of GBRK assets allows the bank to increase lending volumes, the number of financed projects. Most of the projects financed by the GBRC are being implemented in China; the bank is also actively working abroad: it participates in the import of minerals to China, and promotes the export of Chinese goods and services. The experience gained in the implementation of projects in China allows the bank abroad to successfully select projects, carry out their joint financing (taking into account local conditions). The strategically sound selection of projects, their successful implementation in key segments of the Chinese economy, and the growth of the bank’s assets determine the decisive contribution of the GBRC to China’s sustainable economic growth.